Townhouse Culture as a Prison? An Approach to Adosados (Mario Camus, 1996) - García Herrador, María del Pilar (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2022)
The economic boom that Spain experienced in the nineties gave rise to the townhouse culture. The objective is to demonstrate that this culture of the townhouse was used as a control device by the Spanish democratic governments in the 1990s through the urban restructuring of the suburbs of large cities. The cultural analysis of the space of Adosados (Mario Camus, 1996) verifies how the film denounces the control of the subject that is inscribed in standardized parameters from which it seems impossible to escape. Hence, this culture can be compared to the concept of the panopticon theorized by Michel Foucault because, with the gathering of the population in townhouses on the outskirts of large cities, citizens were being reorganized in such a way that their movements and routines were delimited. In this way the middle class is watched and controlled for productive purposes. For this reason, the townhouse is presented as a homogeneous prison from which the protagonist of the film cannot escape.